Thyroid related skin manifestation and their association with autoimmune dermatology - Vartika,; Chahar, Yatendra Singh; Isha Singh,; Goyal, Tanya (International Journal of Research in Dermatology, 2025)
Background: Thyroid disease is associated with changes in hair, skin and nails. which may sometimes be the first clinical clue. A variety of cutaneous findings may present in the setting of either a hyperthyroid or hypothyroid state. Of all the endocrinopathies that might have cutaneous display of dysfunction, thyroid disorders are presumably the most common. Skin conditions and thyroid autoimmunity are strongly linked, according to convincing evidences alopecia areata and vitiligo have the high incidence. The present study is aimed to study various cutaneous manifestations in thyroid disorders and to know various autoimmune and non-autoimmune dermatologic associations of thyroid disorders. Methods: This was a Cross-sectional, observational study with sample size of 400 conducted over a period of 18 months starting from August 2022 to February 2024 in S. N. Medical college, Agra, Uttar Pradesh. All patients with thyroid abnormality and cutaneous manifestations are included in the study. Results: Female preponderance s hypothyroidism hold the major section of thyroid disorders. The most affected age group was 31-40 years. dry skin (67.83%), TE (65.7%) were the commonest symptoms among hypothyroid patients and Warm skin (93.3%) and increased sweating were commonest among hyperthyroid patients. Urticaria (33%) was the most common autoimmune association noted followed by vitiligo (11.75%) and alopecia areata (6.25%) among both hypo and hyperthyroidism patients. Conclusions: This study shows that various cutaneous manifestations be seen in thyroid patients and significant association with autoimmune dermatological disease.